PELUANG DAN TANTANGAN PENGAJARAN AKSARA BALI PADA SISWA MULTIETNIS - Ni Made Ayu Susanthi Pradnya Paramitha; I Nyoman Suka Ardiyasa (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
Teaching Balinese script to multiethnic students faces several challenges including the difficulty of teachers preparing learning tools, so teachers are required to prepare interesting material without having to ignore the learning objectives. In the learning process, students also experience difficulties due to the large number of students who do not have the basics of Balinese script so that it is very difficult for them to take lessons in reading Balinese script, besides that there are many uger-uger Balinese script so that they become confused and have implications for interest in learning Balinese. While the efforts made are trying to prepare learning tools properly, with the hope that students will have more fun in the process of learning to read Balinese scripted texts, the teacher also always provides motivation so that students want to read and learn Balinese script, the teacher seeks to create a conducive learning environment, and the teacher always try to use a variety of teaching methods.Keywords: Balinese language teaching, multiethnic students